Techniques Study for apply Control on Nonlinear Systems and the Concept of the Sliding Mode Control (SMC) - Imad Omar Shebani Etomi; Adel Ali Ramadan Gamati; Ltfei Abdalsmd; Nezar G. Arabi Ayad (Surman Journal of Science and Technology, 2021)
المبادئ الأساسية لهذه الورقة هو دراسة بعض التقنيات المستخدمة لتطبيق التحكم على الأنظمة غير الخطية .و يتم تطبيق هذه الطرق على ثلاثة أمثلة غير خطية مختلفة من أجل التحقق من أداء هذه التقنيات. وكذلك تهدف هذه الورقة إلى فهم مفهوم التحكم في وضع الانزلاق وهناك ثلاث مشاكل يجب حلها لهذه الورقة وهي أولاً التحكم في وضع الانزلاق ، الإحماء و الثاني في وضع الانزلاق لمعادلة فان دير بول (VDP) ، والثالث تحكم (MIMO ) للذراع المستوي ثنائي الوصلة. Abstract: The basic principles of this paper are some techniques that used to apply control on nonlinear systems. These methods were applied to three different nonlinear examples in order to check the performance of these techniques. Moreover, this paper is to understand the concept of the sliding mode control and there are three problems that we should solve for this paper first Sliding Mode Control Warm-Up, second Sliding Mode control for the van der pol Equation (VDP), and third MIMO control of two-link Planar Arm.